Evaluating service users' experiences using Talking Mats®. Issue 2 (3rd April 2018) - Stewart, Kitty; Bradshaw, Jill; Beadle-Brown, Julie
Abstract : Purpose: The purpose of this paper is to establish the effectiveness of Talking Mats® (TM) in evaluating service users' experiences, and explore their views of the implementation of person-centred active support (PCAS). Design/methodology/approach: This is a mixed-methods study, employing qualitative interviewing and observational measures. Findings: Both qualitative and quantitative measures indicated inconsistent implementation of PCAS. It was possible to effectively gain participants' views on positive and negative aspects of quality of support and quality of life, using TM, across three themes, My life, My support and Self-determination. Research limitations/implications: Generalisability of the research may be limited due to the sample, and the potential for researcher and interviewer bias is acknowledged. Practical implications: TM provides a mechanism that may facilitate the inclusion of the views and experiences of people with intellectual and developmental disability (PWIDD) who have limited verbal skills. Their views need to be reflected in adaptions made to PCAS. Originality/value: This study included a population who are often left out of qualitative research because of the methodologies adopted. It also included older PWIDD, where there has been less research about the effectiveness of TM.